Characterisation of structure-borne sound source using reception plate method - Putra, Azma; Saari, Noor Fariza; Bakri, Hairul; Ramlan, Roszaidi; Mat Dan, Reduan (Hindawi Publishing Corporation, 2013)
A laboratory-based experiment procedure of reception plate method for structure-borne sound source characterisation is reported in this paper. The method uses the assumption that the input power from the source installed on the plate is equal to the power dissipated by the plate. In this experiment, rectangular plates having high and low mobility relative to that of the source were used as the reception plates and a small electric fan motor was acting as the structure-borne source. The data representing the source characteristics, namely, the free velocity and the source mobility, were obtained and compared with those from direct measurement. Assumptions and constraints employing this method are discussed.